Health Status Evaluation of Urban Rail Transit Traction Transformers Based on Analytic Hierarchy Process and Entropy Weight Method - ZHANG Mingrui; DUAN Hongwei; XU jie; XU Weijia (Chengshi guidao jiaotong yanjiu)
［Objective］ The purpose of health status evaluation of the traction power supply equipment is to provide references for the operation, repair and maintenance of this equipment in urban rail transit. ［Method］ A health status evaluation model for urban rail transit traction transformer is established based on AHP (analytic hierarchy process) and EWM (entropy weight method). The hierarchical structure for evaluating the health status of the traction transformer is constructed based on the operation indicator data of the traction transformer. The subjective weights of the evaluation indicators are calculated by using AHP through the expert judgment matrix, and the weights of the test indicators are solved by using EWM and then combined with the subjective weights. The health status score of the traction transformer is calculated according to the evaluation indicators to determine its overall health status, thereby predict its remaining service life and evaluate the impact of different maintenance methods on the service life. With the monitoring data of the traction transformer in a certain traction substation as an example, the health status of the traction transformer is evaluated. ［Result & Conclusion］ The effectiveness of the proposed health status evaluation method for traction transformer is verified through examples. The evaluation method realizes unification of the subjective and objective factors of equipment status detection, and can be popularized and applied to the health status evaluation of other urban rail transit DC power supply equipment.